Cognitive Functioning among Older Adults in Japan and Other Selected Asian Countries: In Search of a Better Way to Remeasure Population Aging - NAOHIRO OGAWA; TAIYO FUKAI; NORMA MANSOR; NURUL DIYANA KAMARULZAMAN (Asian Development Review, 2022)
Japan is the oldest society in the world. It has the highest proportion of the population aged 65 and over, a demographic indicator that has been used by demographers for more than a century. One of the main objectives of this study is to apply a new indicator—the cognition-adjusted dependency ratio (CADR)—to remeasure the level of population aging from an innovative point of view. To compute this new index, we apply the mean age-group-specific immediate recall scores for Japan and four other Asian countries, and we compare the results with those derived from the United States and various developed nations in Europe. Our analysis shows that Japan’s pattern and level of age-related decline in cognitive functioning are highly comparable to those of many other developed nations, particularly in Continental Europe. Among the other Asian countries, Malaysia shows a pattern of change similar to countries in Southern Europe, although Malaysia has slightly lower scores than Southern Europe in all age groups. More importantly, these comparative results based on CADR are astonishingly different from the corresponding results obtained from conventional old-age dependency ratios. The Japanese case is the most salient example.